PERANCANGAN SISTEM INFORMASI AKADEMIK BERBASIS WEBSITE MENGGUNAKAN BAHASA PEMROGRAMAN PHP dan MySQL(Studi kasus di SMA Muhammadiyah Imam Syuhodo, Sukoharjo) - Pambayun, Gun; , Much. Djunaidi, S.T., M.T; , Mila Faila Sufa, S.T., M.T (2015)
Online media in the form of a website as a source of information easier for everyone to get information. Through the Internet growing, today one can save time and expense to get the information he needs. Information management in an institution is very important, especially in schools. Where the school will be easier to manage a number of existing data to then be published to the general public. This research aims to design a web-based academic information system conducted at SMA Muhammadiyah Boarding Imam Syuhodo Sukoharjo. In designing an information system is needed for an identification system design, which contains the context diagram, the decomposition process, data flow diagrams and entity relationship diagram. The next steps so that this scheme can work well is to perform database design, form design, report design, and web design and conduct simulations. Based academic information system design of this website using PHP as the programming language and MySQL as the database maker program then simulated through localhost or local server. Based on these results, generated a system of school-based academic information website. The design of this academic information system provides information on the teacher data, student data, school profiles, school agenda, a data value of students as well as photographs of student activities. The system's design also produces two main menus admin menu as manager of information systems, and user pages as recipient information. Keywords: MySQL, PHP, System Information, Website